The Stability of Islamic Banking in Response to Macroeconomic Shocks: An Empirical Study of the Indonesian Islamic Financial Market - Achmad, Achmad; Hayet, Hayet (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2026)
This study aims to examine the influence of macroeconomic variables on the stability of Islamic banking in Indonesia, with Non-Performing Financing (NPF) serving as the primary indicator of banking resilience. A Vector Autoregression (VAR) approach is employed to capture the dynamic interrelationships among variables, including inflation, the exchange rate, the BI Rate, economic growth, and the money supply. Monthly time series data from 2010–2024 were obtained from Bank Indonesia, the Financial Services Authority (OJK), and Statistics Indonesia (BPS). The findings reveal that money supply, exchange rate, and economic growth are the primary macroeconomic determinants of Islamic banking stability in Indonesia. Rapid liquidity expansion and economic growth that are not accompanied by prudent oversight of financing tend to elevate financing risk, while a stable exchange rate plays a critical role in protecting the real sector's repayment capacity. Notably, inflation and the BI Rate do not exert a meaningful short-term influence on NPF, suggesting that Islamic banking operates through a transmission mechanism distinct from its conventional counterpart—one that is less sensitive to interest rate policy. The novelty of this study lies in its use of a comprehensive, long-horizon dataset covering multiple economic cycles, including the 2008 global crisis and the COVID-19 pandemic, which enables a more robust assessment of Islamic banking resilience across varying macroeconomic conditions. The study is limited to macroeconomic variables at the aggregate level and does not account for bank-specific microeconomic factors or regional variations within Indonesia's Islamic banking sector, which may be addressed in future research.